The time course of brain activations during response inhibition: evidence from event-related potentials in a go/no go task - Kiefer, Markus; Marzinzik, Frank; Weisbrod, Matthias; Scherg, Michael; Spitzer, Manfred (Neuroreport, 1998)
THE cortical organization of executive control was investigated using event-related potentials (ERPs). ERPs were collected while subjects performed a go/no go task that required response inhibition. First, around 26ms after stimulus onset, an effect of response inhibition on ERPs was observed over inferior prefrontal areas. Generators in these regions were confirmed by source analysis. Later, between 300-60 ms after stimulus onset, a left lateralized fronto-central ERP effect was found which differed in topography from a non-specific effect of task difficulty. Source analysis indicated that generators in anterior cingulate and left premotor areas also contributed to this effect. Orchestrated activation of prefrontal areas and the anterior cingulate subserves executive function whereas relatively late activity of the left premotor cortex is involved in motor control.
Gesehen am 22.12.2021